The Alternative Profit on Shariah-Compliant by using Compounding Theory - Gazali, Nadhirah; Abdul Halim, Nurfadhlina; Asrul Affendi Abdullah, Mohd; Muhamad Amir W.Ahmad, Wan; Mamat, Mustafa; Abdullah, Zailani; Mokhtar, Kasypi (International Journal of Engineering and Technology, 2018)
Islamic banking and conventional banking has same aim in the financial activity which is to gain profit. Profit of Islamic finance/banking in Malaysia is based on the profit rate, while for conventional banking based on interest rate. However, both profit rate and interest rate are determined based on the same reference rate, namely base rate (BR). The determination of the components contained in the BR such as benchmark cost of funds and the statutory reserve requirement (SRR) found that there is non-compliance with the Shariah perspective because this components directly proportional to the overnight policy rate (OPR). Therefore, an alternative formula for the profit rate was built which is known as the base profit rate (BPR). Form BPR model, determination of the profit based on compounding theory. Thus, construction of BPR formula is based on the principles that are much more Shariah compliant.Â Â